More Than Meets the Eye Evaluating Non-Organic Vision Loss - Ikonomov, Luben M.; Kaufman, Evan J (European Journal of Applied Sciences, 2023)
Non-organic vision loss (NOVL), referred to as “functional vision loss” in the literature, is defined as a decrease in either visual acuity or field of vision without an identifiable underlying organic etiology.1,2 Suspected NOVL requires extensive chair time, increased hands-on care, and reassurance with the patient. NOVL has been found to accompany other organic causes in about 15% of cases.3, 4 A diagnosis of NOVL should be made only after other organic causes of visual loss are ruled out. This may require multiple tests of each part of the visual pathway – many of which are subjective based on patient responses and may therefore yield inconclusive or conflicting results.